Criticizing common sense about war and posthumous harm - Fiala, Andrew G. (Ethical perspectives, 2015)
The present contribution is prompted by Geoffrey Scarre's recent article questioning commemorations of war and the issue of posthumous harm. This is a crucial issue for thinking about the morality of war. In the spirit of commemorating the First World War, which occasioned Scarre's article, I consider the example of Bertrand Russell, whose critique of the common sense of war led him to oppose the First World War and to be jailed for his opposition. Russell offers a perspective that is similar to Scarre's regarding the question of posthumous harm. Russell argues that the question of dying in vain can be used as a tool of war-mongering propaganda. The article considers the general question of "dying in vain". It also argues that the just war theory and pacifism provide critical perspectives that can be used to argue against the irrationality and ruthlessness of wartime propaganda, which often appeals to the idea of posthumous harm to stir up support for war.